Get Out Of The Comfort Zone To The Zone Of Faith - Damayanti Nababan; Fitriyani Elisabet Purba; Seapril SG Manurung; Tiomia Clodianti Tampubolon; Yemima Medina Rista Br. Sembirng; Yohana Olivia Sitorus; Aniela Kristiantri; Reva Yemima Ginting; Santi Lumbanraja; Delceria Sagala; Imelria Simbolon; Risdo Rolita Simanjorang; Yesaya Nababan; Meyke Joice Tresia Rajagukguk; Lastry Panjaitan; Naomi Rose Mariani Silaban; Reza Fahlevi Marbun; Anggun Krisneria Manullang; Feni Sulistiani Sitorus (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2023)
The enemy of progress is comfort. Some people might say, don't we need to feel comfortable in this life? This opinion is not completely wrong, but if we only pursue comfort, then we can get trapped in the comfort zone that we created ourselves. The comfort zone will make a person no longer productive and responsive to change. If someone is trapped in a comfort zone, then their life will quickly decline by it self. This research is motivated by ideal conditions and reality conditions regarding comfort zones and faith zones. The ideal condition is that young Christians must experience a breakthrough in their faith and work for God in accordance with the Bible and the reality is that many young Christians are still tied to their comfort zone. The aim to be achieved in this research is to release Christian youth out of their comfort zone into the faith zone. The research was conducted at the Indonesian Protestant Christian Church with church youth, using qualitative research. Based on research results, many young Christians are still comfortable in their comfort zone. Thus, we raised the title